Implementation of Low-Code Development Platform (LCDP) Appian Designer in the Development of a Waste Bank Application - Hapsari, Yustia; Netanya S, Marsella Lusio; Susilawati, Agnes Dwita; Ujianto, Nur Tulus; Sumarno, Sumarno (Journal of Artificial Intelligence and Software Engineering, 2025)
Waste management issues, particularly in the areas of record-keeping and transaction management within Waste Banks, remain a challenge in communities. This study aims to develop a digital-based Waste Bank  application using the Low-Code Development Platform (LCDP) Appian Designer. The method applied is Rapid Application Development (RAD), which supports rapid iteration and flexible interface development. The research stages include requirements planning, interface design, system construction, and performance testing. Thefeature requirements were designed in a relational database structure and implemented in Appian. Performance testing using Appian's built-in tools showed that the render times for the login, waste deposit, and withdrawal forms were only 3 milliseconds, registration 14 milliseconds, and report and resident menu forms 4 milliseconds. These results indicate that all forms exhibit responsive and stable performance. Appian has proven capable of delivering applications with lightweight and fast user interfaces. The use of RAD through the InterfacePerformance View feature accelerates the development process while maintaining system quality. In conclusion, this approach is effective in supporting the digitalization of Waste Bank management in a more systematic, efficient, and sustainable manner.